Utilization of Food Processing Technologies by Women Farmers in Umuahia Agricultural Zone, Abia State, Nigeria - F. C, Nzeakor; J. C. I, Ukoha (Journal of Food Technology Research, 2020)
The study focused on the utilization of food processing technologies by women farmers in Umuahia Agricultural zone, Abia State, Nigeria. A multistage sampling technique was used in selecting 120 farmers that participated in the study. Information was obtained through structured questionnaire. Both descriptive and inferential statistics were used in analyzing the data. Major results showed that the mean age and years of farming experience of farmers were 42 years and 11 years respectively, the mean income of vegetable farmers per month was N23, 375.33. Furthermore, the result showed the respondents had a mean household size of 7persons with over 95% of them having one form of education or the other. About six different food processing technologies were disseminated to farmers, out of which, five were highly utilized with a grand mean score of 3.1 on a 4-point scale. The technology on processing cassava into odourless fufu was highly utilized with a mean score of 3.5 while the technology on processing tumeric into drink had low utilization (x̄=2.3). Major factors that positively influenced effective utilization of food processing technologies include Easy understanding and application of technologies (x̄=3.3), Frequency of extension contacts (x̄=3.1), Availability of food crops (x̄=3.1), Increased income from sales (x̄=3.3) among others. The inferential result showed that there is a relationship between the women farmers’ age and their level of utilization of the processing technologies in the study area. It is therefore recommended that government should assist the women to access credit facilities to boast their processing enterprise.